THE EFFECT OF INSTRUCTIONAL MODELS AND LEARNING STYLES TOWARDS WRITING SKILL - Nisa, Baiatun (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2016)
The objective of this experimental study is to find out the effect of instructional models and learning styles toward learnersâ English writing skill. The research was conducted at the English Department, the Academy of Foreign Language BSI Jakarta Indonesia. The results of this research indicated that: (1) there is a significant different improvement of English writing skill between group of learners who were taught by using the STAD Cooperative Learning model and those who were taught by using The Lecture Model, (2) English writing skill of the visual learners taught by using STAD Cooperative Learning model is better than those taught by using The Lecture Model, (3) English writing skill of the auditory learners taught by using The Lecture Model is better than those taught by using STAD Cooperative learning model, and (4) there is an interaction effect between the instructional model and learning style towards English writing skill achievement.